Illusion of life in Bob Dylan's "murder most foul". (3rd April 2022) - Franken, Noah; Hanson, Trudy L.
ABSTRACT: This article examined the Bob Dylan song, "Murder Most Foul, " using the illusion of life rhetorical perspective. The song's music and lyrics together speak to an American experience defined by the fallout of the JFK assassination: a public consumed with doubt, distrust, and conspiracy; however, a public that can perhaps still spark change. Overall, the song presents an incongruity between music and lyrics whereby the quietness of the music is at odds with the horrible scene recreated for the listener lyrically. In the song, the dramatic illusion is overtaken by the poetic, and the comic rhythm is flooded by the tragic. Concurrently, in the virtual time, optimism is overtaken by tragedy, life gives way to death, and death becomes release and transformation. The song, without a chorus and 17-minutes long, represents an unfamiliar form of song containing elements of the murder and apocalyptic ballad as well as protest music.